2000
DOI: 10.1046/j.1365-4362.2000.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitiligo in lepromatous leprosy

Abstract: Our data confirmed that the association of vitiligo and leprosy was not fortuitous. The physiopathology leading to this high rate of vitiligo in lepromatous leprosy is unclear, despite the fact that autoimmunity plays a major role in both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…But, we might first question whether microbial changes have been associated with melanoma or vitiligo (Gudjonsson et al., 2020). The association between microbes and progressive depigmentation stands out when we realize that vitiligo is approximately 10‐fold more prevalent among lepromatous leprosy patients (Boisseau‐Garsaud et al., 2000). This relationship would make vitiligo seem contagious, explaining why vitiligo can be so stigmatizing in locations where leprosy exists (Pahwa et al., 2013).…”
Section: Environmental Insults Impact Microbial Homeostasismentioning
confidence: 99%
“…But, we might first question whether microbial changes have been associated with melanoma or vitiligo (Gudjonsson et al., 2020). The association between microbes and progressive depigmentation stands out when we realize that vitiligo is approximately 10‐fold more prevalent among lepromatous leprosy patients (Boisseau‐Garsaud et al., 2000). This relationship would make vitiligo seem contagious, explaining why vitiligo can be so stigmatizing in locations where leprosy exists (Pahwa et al., 2013).…”
Section: Environmental Insults Impact Microbial Homeostasismentioning
confidence: 99%
“…Corcos 82 studied how the depigmentation spread, and concluded that it was not passed from one cell to another but that it is brought about by extra bacillary proliferation of a subcellular, selfreplicating agent initially carried by mycobacteria, rather than by the mycobacteria themselves. In leprosy, the lepromatous end of the spectrum is 11 times more likely to be associated with vitiligo than is tuberculoid leprosy 83 . It has been most recently demonstrated that Mycobacterium leprae alters the genetics of Schwann cells without even penetrating their nuclei and this activates genes that convert the cell into a neural crest stem cell, shielding the bacteria from destructive elements 84 .…”
Section: Leprosymentioning
confidence: 99%
“…The study was carried out in the only reference hospital for the follow-up of leprosy patients in Martinique, a place with a highly endemic leprosy. No patient from the tuberculoid pole had vitiligo 10 .…”
Section: Introductionmentioning
confidence: 96%